(untitled) (Research, Society and Development, 2021)
Affection has an important role in the human being’s learning process. With the help of affection, teachers and students are able to create bonds of friendship with each other. It empowers the human being to reveal his feelings in relation to other beings and objects. Based on these assumptions, this article aims to discuss an analysis of the importance of the affective aspect and social interaction experienced by young people and adults in the classroom during the literacy process. This research presents a qualitative methodology within an exploratory bibliographic perspective, in which the denoted data were analyzed based on the perspective of the Document Analysis Method, which consists in extracting informational elements from an original document in order to express its content in a abbreviated, resulting in the conversion of a primary document into a secondary document. In the data obtained, it can be inferred that the relationships established in the classroom constitute one of the most significant moments for the expression of affectivity, thus contributing to the development of the student’s constitution as a person.